2015
DOI: 10.1097/jom.0000000000000395
|View full text |Cite
|
Sign up to set email alerts
|

Physical Capacity and Risk for Long-Term Sickness Absence

Abstract: Low physical capacity increases the risk of long-term sickness absence among female health care workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…, and one study (Roelen, van Rhenan, et al, 2013) performed a secondary analysis of data from a longitudinal survey (Roelen, Bültmann, et al, 2013). Primary studies had a variable followup period, but most studies had a follow-up period of approximately 1 year (Bourbonnais & Mondor, 2001;Chan, 2007;Demerouti et al, 2009;Rasmussen et al, 2015;Rauhala et al, 2007;Roelen, van Rhenan, et al, 2013;Roelen, Bültmann, et al, 2013;Van Buynder et al, 2015).…”
Section: Bourbonnais and Mondor (2001) Job Strain (High Pd And Low Dl)mentioning
confidence: 99%
See 2 more Smart Citations
“…, and one study (Roelen, van Rhenan, et al, 2013) performed a secondary analysis of data from a longitudinal survey (Roelen, Bültmann, et al, 2013). Primary studies had a variable followup period, but most studies had a follow-up period of approximately 1 year (Bourbonnais & Mondor, 2001;Chan, 2007;Demerouti et al, 2009;Rasmussen et al, 2015;Rauhala et al, 2007;Roelen, van Rhenan, et al, 2013;Roelen, Bültmann, et al, 2013;Van Buynder et al, 2015).…”
Section: Bourbonnais and Mondor (2001) Job Strain (High Pd And Low Dl)mentioning
confidence: 99%
“…The number of included participants was also variable and ranged from 73 in a study where employers of only one department were followed (Chan, 2007) to 107 209 in a panel study (Kjekshus et al, 2014) where data for employers of 57 hospitals were collected. Three studies (Jensen et al, 2010;Roelen, van Rhenan, et al, 2013;Roelen, Bültmann, et al, 2013) assessed the impact of physical and mental functions on sickness absence; one study (Rasmussen et al, 2015) only investigated the impact of physical capacity on sickness absence. Two studies (Bourbonnais & Mondor, 2001;Rauhala et al, 2007) examined the association between work factors and SA, and 2 studies (Chan, 2007;Van Buynder et al, 2015) exclusively assessed influenza vaccination on SA.…”
Section: Characteristics Of the Included Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…These inconsistencies may, in part, be attributed to the use of different assessment methods, including subjective assessments and observation (Aittomaki et al 2005; Burr et al 2017; Rasmussen et al 2015; Torgen et al 1999). These methods are characterised by recall and (self-)estimation bias; for valid assessments, objective measures are preferred (Koch et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, reasons for lower sickness absence among intervention group remains unclear. According to Rasmussen et al [38] high self-reported physical capacity was associated with lower long-term sickness absence among female health care workers. However, information on our study participant’s current physical capacity was not available.…”
Section: Discussionmentioning
confidence: 99%